2016
DOI: 10.2147/copd.s109707
|View full text |Cite
|
Sign up to set email alerts
|

The burden of chronic obstructive pulmonary disease associated with maintenance monotherapy in the UK

Abstract: BackgroundThis study characterized a cohort of chronic obstructive pulmonary disease (COPD) patients on maintenance bronchodilator monotherapy for ≥6 months to establish their disease burden, measured by health care utilization.MethodsData were extracted from the UK Clinical Practice Research Datalink and linked to Hospital Episode Statistics. The monotherapy period spanned the first prescription of a long-acting β2-adrenergic agonist or a long-acting muscarinic antagonist until the end of the study (December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In this claims-linked survey study assessing patient-reported symptoms and burden of illness among patients with COPD treated with LAMA monotherapy, COPD had a considerable impact on patient well-being and was associated with substantial resource burden. These results are consistent with observations from previous studies which have reported that patients receiving long-acting bronchodilator monotherapy continued to experience a high symptom burden, had recent exacerbations and exhibited poor QoL, and had a higher than average rate of physician interactions [9,24]. The majority of patients in this study experienced substantial symptom burden as measured by multiple PROs; in particular, there were high levels of dyspnea, with almost half of the patients experiencing severe dyspnea using the definitions presented in the GOLD strategic report [2].…”
Section: Discussionsupporting
confidence: 91%
“…In this claims-linked survey study assessing patient-reported symptoms and burden of illness among patients with COPD treated with LAMA monotherapy, COPD had a considerable impact on patient well-being and was associated with substantial resource burden. These results are consistent with observations from previous studies which have reported that patients receiving long-acting bronchodilator monotherapy continued to experience a high symptom burden, had recent exacerbations and exhibited poor QoL, and had a higher than average rate of physician interactions [9,24]. The majority of patients in this study experienced substantial symptom burden as measured by multiple PROs; in particular, there were high levels of dyspnea, with almost half of the patients experiencing severe dyspnea using the definitions presented in the GOLD strategic report [2].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are comparable to a 2016 study conducted in the UK (n=8,811 COPD patients) where 10% of patients experienced a COPD exacerbation and 2% were hospitalized for COPD. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even using only the history of exacerbations, very severe COPD is two times more frequent in patients treated with LABA+LAMA versus LAMA (7.9% vs. 3.2%). A feasible explanation for this is that patients with noncontrolled disease (including persistent exacerbations) more frequently receive LABA‐LAMA therapy [6].…”
mentioning
confidence: 99%